Electric Drive Units: A Set-Up for Investigating Function, Efficiency, and Dynamics - Pointner-Gabriel, Lukas; Franzelin, Thomas; Morhard, Bernd; Schweigert, Daniel; Voelkel, Katharina; Stahl, Karsten (Vehicles, 2024)
High-speed electric drive units promise improved power density and, theoretically, driving range of battery electric vehicles. An essential step of the development process is extensive testing of the drive unit on a test rig. In particular, at a high rotational speed level, experimental testing can be challenging. This paper describes a test rig for investigating the overall function of a high-speed drive unit and the transmission’s efficiency and dynamics. The high-speed drive unit developed in the Speed4E research project was the reference drive unit. The test rig is based on the concept of electrical power circulation. Thus, the test rig can be used universally for different drive unit designs and operating modes. A reaction torque measurement unit was developed to enable measurements at high rotational speeds. Simultaneously, this unit allows robust measurements at low costs. The expected measurement uncertainties of torque, rotational speed, transmission efficiency, and power losses were calculated using the Monte Carlo method. The results demonstrate that the developed torque measurement unit combines precise torque measurement with a robust design and low costs, making it competitive with state-of-the-art solutions for torque measurement at high speeds.
CRIS-Team Scopus Importer:2025-05-19
Keywords: electric drive units; electric vehicles; experimental testing